PENGARUH KOMPENSASI DAN FASILITAS KERJATERHADAP KEPUASAN KERJA GURU PADA SMK GKPS 2 PEMATANGSIANTAR - Nainggolan, Debora; Lie, Darwin; Butarbutar, Marisi; Sisca, Sisca (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2018)
The purpose of this study are: 1. To determine the description of compensation, jobfacilities and teacher job satisfaction at SMK GKPS 2 Pematangsiantar Pematangsiantar. 2. To determine the influence of compensation and job facilities of teacherjob satisfaction at SMK GKPS 2 Pematangsiantar either simultaneously or partially.The research was done by using literature and field research. This study used source data are primary data and secondary data. The type of data used quantitative and qualitative data as of 59 respondents areteacher of SMK GKPS 2 Pematangsiantar. Collecting data done by questionaires, interviews and documentations. The analysis technique has done by regression multiple linear, coefficient correlation and determination with testing hypothesis with test F and test t.                The result of this research can be summarized as followsŶ = 9,708 + 0,170X1 + 0,162X2,  meaningcompensation and job facilities has positive influence to job satisfaction. The result of analysis correlations r = 0,673 it means that there is moderately correlation between being and compensation and job facilities to job satisfaction. Then obtained the value of coefficient of determination = 0,453, it means employees  performance can be explained by 45,3% by compensation and job facilities. Hypothesis H0is rejected, it means the compensation and job facilities haspositive and significant influence to teacher job satisfaction at the SMK GKPS 2 Pematangsiantar either simultaneously or partially.  Keywords: Compensation, job facilities and teacher job satisfaction